Relationship between leader-member exchange and burnout in professional footballers - Yildiz, S. M. (Journal of Sports Sciences, 2011)
Numerous variables influence burnout, one of which is leader-member exchange. The present study was conducted to determine whether leader-member exchange quality affects burnout in professional footballers. The study used the Leader-Member Exchange-7 scale developed by Scandura and Graen (1984) to measure leader (coach)-member (player) exchange and Pines's (2005) abbreviated version of the burnout scale developed by Pines and Aronson (1988) to measure burnout. The data were obtained from the professional players (N = 107) of six football clubs in the Turkish Secondary Football League in western Turkey. The results demonstrated that quality of leader-member exchange significantly and inversely influenced burnout of professional footballers. The study also evaluated quality of leader-member exchange in terms of three strengths of relationship (low, fair, and high) between the coach and players. Contrary to expectations, the results revealed significant differences in burnout when comparing low versus fair quality and low versus high quality, while no significant difference in burnout was observed between fair and high quality.